ANALISIS EFEKTIVITAS DAN KONTRIBUSI PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN MALANG - Ummu Kalsum Ismanura; Jeni Susyanti; M. Agus Salim (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThe aim of this study is to know the level of effectiveness and how huge the contribution restaurant, hotel, advertisement tax toward original income in Malang regency during three years ago (2016-2018). This study used descriptive qualitative data. The researcher gets the data with documentation method obtained from Regional Revenue Agency (Badan Pendapatan Daerah). The result of this study showed that (1) the effectivess of the restaurant tax 2016-2018 is very effective criteria. The effectiveness of the hotel tax 2017-2019 is very effective. And effectiveness of advertisement tax 2017-2019 is very effective. The effectiveness of retributin region is very effective. (2) The contribution of revenue restaurant tax 2016-2018 is very less. The contribution of hotel tax 2016-2018 is very less and the region contribution 2016-2018 is very less criteria.Keywords: local tax, regional retribution, local original income, effectiveness, and contribution